Development of Student Worksheet with Guided Inquiry to Train High Order Thinking Skills on the Reaction Rate Materials - Fairuziyah Aizzatun Nisa; Harun Nasrudin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aimed to know the feasibility of the students' worksheets with guided inquiry to train high-order thinking skills on the reaction rate materials. The research method used is Research and Development by Borg & Gall until the limited trial stage. The limited trial was conducted on 33 students in class XI IPA 1 SMAN 1 Gedangan Sidoarjo. The student worksheets with guided inquiry are feasible based on validity, practicality, and effectiveness aspects. Aspects of validity include content validity and construct validity indicate that the student worksheet developed is very valid with a percentage of 93% and 89.70% for each criterion. Practicality observed from the results of the student response questionnaires gets a percentage of 94-100% with a very practice category and supported by more relevant student activities than irrelevant activities. The effectiveness is seen from the results of the knowledge domain test and HOTS with Paired Sample T-Test each getting a Sig. (2-tailed) of 0.000 which means the difference in the average value between before and before the student worksheet was given. In addition, the effectiveness is also viewed from the n-gain. The n-gain results on the knowledge domain test showed 84.84% of students with high category and 15.16% of students with medium category, and the n-gain results on the HOTS test showed 93.93% of students with high category and 6.07% of students with medium category. So, it can be stated that the student worksheet with guided inquiry is declared feasible and can train students' HOTS.